Emotional Abuse to Early Elementary School Students as Perceived by Class Teachers, Principals, and School Counselors: A Comparative Study - Bani-Ahmad, Asma; Farah, Adnan (Jordan Journal of Educational Sciences, 2007)
The main objective of this study was to investigate class teachers’, school counselors’ and school principals’ perception of child emotional abuse embedded in the activities of class teachers. The perception of the three groups was compared internally on one hand, and externally with a reference group on the other. To achieve this purpose, 40 schools out of 55 in the First and Second Irbid Directorates which have the first three classes and a counselor were semi-randomly selected. Three class teachers were selected from each school and a sample of 20 yarmouk university faculty members were selected to form the reference group. Child emotional abuse scale was constructed based on literature review and child abuse scales in general which include varieties of items or subscales of emotional child abuse. The procedures of construction support the validity and reliability of the scale which has in its final form 53 items, each of 5 ratings (extreme abuse, significant abuse, low abuse ,slight abuse, and no abuse) covering many aspects like degrading ,terrorizing disciplining, ignoring, rejection, isolation, denying emotional responsiveness ,corruption dissocializing, exploiting ,and over-expectation. The literature of this study and the procedures of this scale construction revealed that developing or constructing a unique emotional child abuse is an important step in the field of research in this track. The scale was administered to the sample which eventually contained 108 class teachers, 34 counselors, and 36 principals. The data of ratings were statistically and logically manipulated, then many conclusions were drawn and recommendations were advanced. The means of ratings of the four groups show that all the scale items were charged by some specific level of emotional abuse. The reference group was highlighted by ten items of extreme emotional abuse with the highest average within 3.0 to 3.4 subintervals, while the means of the other three groups were within lower subinterval from 2.5 to 2.5. The variance of ratings was statistically different: the variance of the reference group shows that ratings were highly homogenous compared to the counterpart variance of the other three groups. From another point of view, the real ratings means were statistically compared with the hypothesized scale mean. The results revealed that the seeds of emotional child abuse exist in thinking and perception through verbal and non-verbal acts of class teachers. These seeds may grow if this kind and level of perception is negatively supported by similar perception of counselors or/and principals .Many items were rated by class teachers revealing that it is considered as normal behavior which is the opposite of the perception of the other groups from a relative points of view. But the results in general reveal that the roles of school counselor and school principals compared with the local reference group should be more sensitive to the side effects of child emotional abuse.